Oncological impact of inflammatory biomarkers in elderly patients treated with radical cystectomy for urothelial bladder cancer. Issue 1 (2nd January 2021) - Mari, Andrea; Muto, Gianluca; Di Maida, Fabrizio; Tellini, Riccardo; Bossa, Riccardo; Bisegna, Claudio; Campi, Riccardo; Cocci, Andrea; Viola, Lorenzo; Grosso, Antonio; Scelzi, Sabino; Lapini, Alberto; et al.
ABSTRACT: Objective: To evaluate the impact of preoperative markers of systemic inflammation on complications and oncological outcomes in patients aged ≥75 years treated with radical cystectomy (RC) for urothelial bladder cancer (UBC). Patients and methods: The clinical data of 694 patients treated with open RC for UBC at our institution between January 2008 and December 2015 were retrospectively reviewed. Patients aged <75 years, with distant metastases, other-than-urothelial histological type, comorbidities that could affect the systemic inflammatory markers, and patients who received neoadjuvant chemotherapy were excluded. Multivariable regression models were built for the prediction of major postoperative surgical complications, disease recurrence, cancer-specific mortality (CSM), and overall mortality (OM). Results: The median (interquartile range [IQR]) age at surgery was 79 (75–83) years. Major postoperative surgical complications were registered in 41.9% of the patients. The 5-year overall survival, cancer-specific survival and recurrence-free survival rates were 42.4% (95% confidence interval [CI] 34.7–49.9%), 70.3% (95% CI 62.3–76.9%), and 59.8% (95% CI 52.4–66.5), respectively. At multivariable analysis, higher levels of fibrinogen and a modified Glasgow Prognostic Score (mGPS) of 1 and 2 at baseline were independently associated with higher risk of major postoperative complications and of CSM. The inclusion of mGPS and fibrinogen to a standard multivariable model for recurrence and for CSM increased discrimination from 69.4% to 73.0% and from 71.3% to 73.9%, respectively. Preoperative neutrophil-to-lymphocyte ratio of >3 was independently associated with OM (hazard ratio 1.38, 95% CI 1.01–1.77; P = 0.01). Conclusions: In a cohort of elderly patients with UBC treated with RC, fibrinogen and mGPS appeared to be the most relevant prognostic measurements and increased the accuracy of clinicopathological preoperative models to predict major postoperative complications, disease recurrence and mortality. Abbreviations: ASA: American Society of Anesthesiologists; CCI: Charlson Comorbidity Index; CIS: carcinoma in situ ; CRP: C-reactive protein; CSM: cancer-specific mortality; CSS: cancer-specific survival; ECOG PS: Eastern Cooperative Oncology Group Performance Status; HDL: high-density lipoprotein; (S)HR: (subdistribution) hazard ratio; LND: lymphadenectomy; LVI: lymphovascular invasion; mGPS: modified Glasgow Prognostic Score; NLR: neutrophil-to-lymphocyte ratio; NOC: non-organ-confined; OM: overall mortality; OR: odds ratio; OS: overall survival; RC: radical cystectomy; RNU: radical nephroureterectomy; UBC: urothelial bladder cancer; UTUC: upper urinary tract urothelial carcinoma